THE CONCERNS OF CANADIAN WOMEN ACADEMICS: WILL FACULTY SHORTAGES MAKE THINGS SETTER OR WORSE? - Acker, Sandra (McGill Journal of Education / Revue des sciences de l’éducation de McGill, 2003)
ABSTRACT. The purpose of this article is to apply a gender analysis to a predicted trend in Canadian academic life, the expected decline in faculty numbers over the coming decades as new faculty numbers do not keep pace with retirements of the baby-boom generation. The first section develops the notion of a gender analysis and gives a brief summary of my own research on Canadian women academics. The next section describes the "faculty shortage problem" and its likely impact on Canadian higher education. Then the two topics are brought together by questioning how the shortages might impact upon the concerns of women academics. Here I imagine three scenarios based on different ways governments and universities might respond to the issue. The article concludes with a consideration of what a gender analysis has told us about the predieted faculty shortage problem. LES INQUIÉTUDES DES FEMMES CANADIENNES POSSÉDANT DES DIPLOMES UNIVERSITAIRES; LA PÉNURIE DANS LES FACULTÉS AMÉLIORERA-T-ELLE OU AGGRAVERA-T-ELLE LES CHOSES? RÉSUMÉ. Le but de cet article est d’appliquer une analyse des questions de parité à une tendance prévue dans la vie universitaire, soit le déclin attendu dans les facultés au cours des prochaines décennies en raison des départs à la retraite de la génération des baby-boomers. La première section explore en détail l’idée d’une analyse des données en fonction du sexe et contient un bref sommaire de ma propre recherche sur les femmes universitaires canadiennes. La section suivante décrit le «problème de pénurie dans les facultés» et ses répercussions possibles sur l’enseignement supérieur au Canada. Les deux sujets sont ensuite réunis afin d’analyser de quelle façon la pénurie peut se répercuter sur les préoccupations des femmes universitaires. J’élabore trois scénarios fondés sur différentes solutions que peuvent envisager les gouvernements et les universités pour résoudre ce problème. Dans sa conclusion, l’article se concentre sur ce qu’une analyse des questions de parité nous renseigne sur la pénurie prévue dans les facultés.